Efforts to Increase Mathematics Learning Motivation through ICT-Based Interactive Media for Fourth Grade Students of SD Negeri 15 Banda Aceh - Wardah, Raudhatul; Safrina, Merry (MANDAILING GLOBAL EDUKASIA, 2025)
This study employed a Classroom Action Research (CAR) methodology across two cycles to investigate the effectiveness of ICT-based interactive media in boosting mathematics learning motivation among fourth-grade students (N=32) at SD Negeri 15 Banda Aceh. The initial observation indicated low student motivation, characterized by passive participation, lack of engagement in problem-solving, and a class average motivation score of only 58.5%. This situation necessitated an innovative teaching intervention focusing on motivational factors. The intervention involved integrating digital games, interactive simulations, and visually appealing multimedia content during mathematics lessons, specifically structured to align with cooperative learning principles. Data were collected using questionnaires for learning motivation (pre-cycle, Cycle I, and Cycle II) and observational sheets for student engagement. Results showed a marked improvement in motivation post-intervention. In Cycle I, the average motivation score increased to 75.2%, indicating that the novelty and interactive nature of the media successfully stimulated interest. Following refinements in Cycle II, particularly emphasizing peer collaboration facilitated by the media, the average motivation score further rose to 88.9%. This final achievement exceeds the established success indicator of 80%. The study concludes that the application of ICT-based interactive media is highly effective in increasing the mathematics learning motivation of fourth-grade students. The interactivity and visualization capabilities of the digital media successfully transformed the learning environment from teacher-centered to student-centered, consequently improving engagement and intrinsic drive towards the subject. This approach is recommended for other primary schools seeking to tackle motivational deficits in abstract subjects like mathematics.